2019
DOI: 10.1128/aac.02674-18
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Biosynthetic Pathways Are Required for Klebsiella pneumoniae Growth in Immunocompromised Lungs and Are Druggable Targets during Infection

Abstract: The emergence of multidrug-resistant Klebsiella pneumoniae has rendered a large array of infections difficult to treat. In a high-throughput genetic screen of factors required for K. pneumoniae survival in the lung, amino acid biosynthesis genes were critical for infection in both immunosuppressed and wild-type (WT) mice. The limited pool of amino acids in the lung did not change during infection and was insufficient for K. pneumoniae to overcome attenuating mutations in aroA, hisA, leuA, leuB, serA, serB, trp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Amino acid profiling of the extracellular lung contents revealed that histidine and other amino acids are detectable, and likely bioavailable, to A. baumannii and other bacterial pathogens. The levels of histidine and several amino acids did not significantly change with infection, which is consistent with metabolite analysis performed on BALF following Klebsiella pneumoniae infection (24). However, other amino acids did change with infections status, such as glutamine and glutamate, which are known modulators of macrophage activity (25).…”
Section: Discussionsupporting
confidence: 73%
“…Amino acid profiling of the extracellular lung contents revealed that histidine and other amino acids are detectable, and likely bioavailable, to A. baumannii and other bacterial pathogens. The levels of histidine and several amino acids did not significantly change with infection, which is consistent with metabolite analysis performed on BALF following Klebsiella pneumoniae infection (24). However, other amino acids did change with infections status, such as glutamine and glutamate, which are known modulators of macrophage activity (25).…”
Section: Discussionsupporting
confidence: 73%
“…Yeast cultures were grown overnight in liquid YPD at 30°C with shaking, washed twice in PBS, counted with the hemocytometer, and resuspended in PBS ( Negoro et al., 2020 ; Xu et al., 2018 ). MKP220, a streptomycin-resistant, capsule type K2 derivative of K. pneumoniae ATCC43816 was grown overnight in liquid LB at 37°C with aeration ( Silver et al., 2019 ; Nguyen et al., 2020 ; Paczosa et al., 2020 ). Overnight cultures were used for in vivo infections.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, glyphosate inhibited C. neoformans growth and production of melanin, a compound necessary for virulence (Nosanchuk et al 2001). Likewise, in mice, intranasal spraying of glyphosate limited an infection by Klebsiella pneumoniae (commensal bacterium in the intestine, but pathogenic elsewhere) (Silver et al 2019). Though aware of the hazards from the use of glyphosate as a treatment, the authors acknowledged that the agent could be a useful tool to test the therapeutic potentials of drugs that could target aromatic amino acid production.…”
Section: Interactions With Pathogen Infectionsmentioning
confidence: 99%